L-Phenylalanine Transport in Saccharomyces cerevisiae: Participation of GAP1, BAP2, and AGP1 - Stella, Carlos Alberto (2014)
We focused on the participation of GAP1, BAP2, andAGP1 in L-phenylalanine transport in yeast. In order to study the physiological functions of GAP1, BAP2, and AGP1 in L-phenylalanine transport, we examined the kinetics, substrate specificity, and regulation of these systems, employing isogenic haploid strains with the respective genes disrupted individually and in combination. During the characterization of phenylalanine transport, we noted important regulatory phenomena associated with these systems. Our results show that Agp1p is the major transporter of the phenylalanine in a gap1 strain growing in synthetic media with leucine present as an inducer. In a wild type strai